Structure of the pellucid septum and its relation to the corpus callosum - Boiagina, O. D.; Kostilenko, Yu. P. (Journal of Education, Health and Sport, 2016)
Boiagina O. D., Kostilenko Yu. P. Structure of the pellucid septum and its relation to the corpus callosum. Journal of Education, Health and Sport. 2016;6(12):895-905. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.258355 http://ojs.ukw.edu.pl/index.php/johs/article/view/4192 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.12.2016. Revised 20.12.2016. Accepted: 25.12.2016. UDK 611.813.9 STRUCTURE OF THE PELLUCID SEPTUM AND ITS RELATION TO THE CORPUS CALLOSUM O. D. Boiagina1, Yu. P. Kostilenko2 1Kharkiv National Medical University Department of Human Anatomy 2HSEIU "Ukrainian Medical Stomatological Academy" Department of Human Anatomy Abstract Objective.The aim is to study the microscopic structure of the pellucid septum and to determine the essence of its anatomical connection with the corpus callosum. Methods. The material used was the medial total mounts of the corpus callosum (together with the pellucid septum and fornix formations) of 10 men aged 36 to 60 years. These total mounts were subjected to complete plastination in epoxy resin, followed by making polished thin sections stained with 1% methylene blue solution on 1% borax solution. Results. As a result of the research, the failure of existing concept of the pellucid septum as a conductive formation in the limbic system of the brain based on the fact that it does not have myelinated nerve fibers was substantiated for the first time. This formation is of purely glial nature, being directly related to the internal limiting glial membrane, which covers the brain substance from its ventricles. It is also found that the venous vessels of the pellucid septum are the main collectors for the blood flowing from the corpus callosum. Keywords: the corpus callosum, the pellucid septum, the limbic brain, epoxy plastination.